Simple, Economic, and Robust Rail-Based Setup for Super-Resolution Localization Microscopy - Almahayni, Karim; Almahayni, Karim; Nestola, Gianluca; Spiekermann, Malte; Möckl, Leonhard (Journal of Physical Chemistry A, 2023)
Research during the past 2 decades has showcased the power of single-molecule localization microscopy (SMLM) as a tool for exploring the nanoworld. However, SMLM systems are typically available in specialized laboratories and imaging facilities, owing to their expensiveness as well as complex assembly and alignment procedure. Here, we lay out the blueprint of a sturdy, rail-based, cost-efficient, multicolor SMLM setup that is easy to construct and align in service of simplifying the accessibility of SMLM. We characterize the optical properties of the design and assess its capabilities, robustness, and stability. The performance of the system is assayed using super-resolution imaging of biological samples. We believe that this design will make SMLM more affordable and broaden its availability.
CRIS-Team Scopus Importer:2023-06-09